The Impact of the COVID-19 Pandemic on Lifestyle and Wellbeing of Children, Adolescents and Their Parents: A Qualitative Study - Kelly G. H. van de Pas; Marijn L. Hesselink; Robin Schlechtriem; Lisanne Arayess; Johanna M. Kreutz; Anita C. E. Vreugdenhil (MDPI AG, 2022)
Prior studies have shown that changes in daily structure and habits due to the COVID-19 pandemic affected the lifestyle and wellbeing of families. This study aimed to obtain in-depth information on children's and adolescents' experiences regarding their lifestyle and wellbeing during the pandemic. Semi-structured interviews with fifteen families were carried out between May and November 2021. Directed content analysis was used to analyze the transcripts and fundamental qualitative description to describe the results. Children and adolescents revealed an overall unhealthier lifestyle and decreased wellbeing. These negative effects were even larger in adolescents and children with overweight or psychosocial complaints. Our results revealed that parents were actively involved in maintaining a normal daily structure. Furthermore, diet changes were inconsistent and dependent on food availability. An increase in screen time was experienced as inevitable, and external influences were necessary to keep children and adolescents active. Almost no effects were reported on physical health, whereas negative emotions were experienced in varying degrees. Moreover, the decrease in social interactions was reported as the most negative effect of the pandemic. The above-mentioned insights may contribute to the development of preventive measures to promote a healthy lifestyle and wellbeing of children and adolescents during future pandemics.